An unexpected risk: Surgical procedures are common in patients with prion disease. (31st December 2021) - Prusinski, Christian C; Porter, Amanda; Lazar, Evelyn; Yuh, Clara; Bucelli, Robert C; Day, Gregory S
Abstract: Background: Patients with prion disease commonly present with visual, sensorimotor or gait complaints that may prompt surgical interventions for related disorders (e.g., cataracts, carpal tunnel syndrome and joint disease). To prevent iatrogenic transmission of prion disease, surgical instruments used on patients with possible prion disease must be decontaminated or decommissioned. This is only done when the diagnosis of possible prion disease is recognized by the healthcare team. We considered the frequency with which patients with definite or probable prion disease underwent surgeries within one year of the symptomatic onset of prion disease diagnosed. Method: The Mayo Clinic's Advanced Cohort Explorer was used to identify patients with prion disease diagnostic codes assessed since 1/1/2014 (n=296). Patients with prion disease enrolled in prospective studies of rapidly progressive dementia beginning 2/14/2015 at Washington University School of Medicine (St. Louis, MO) were also included (n=14). Charts were independently reviewed by two team members, and demographic and clinical details extracted. Result: 108 patients with probable or definite prion disease were identified, including 62 (57%) with autopsy‐ or genetically‐proven prion disease (57 sporadic, 4 familial, 1 fatal familial insomnia). The majority of patients experienced a rapidly progressive course (mean symptom‐duration 10.0±9.7 months). Twenty‐nine patients (26.9%) underwent 36 surgeries or invasive procedures using durable instruments, including 3 high‐risk procedures directly involving the central nervous system, and 13 intermediate‐ (e.g., joint replacement) and 20 low‐risk procedures (e.g., endoscopy). Surgeries were performed a median of 10.2 months before death (range: 0.8‐62.3), with 16 (44%) performed after symptom onset. Surgical operators were unaware of the diagnosis of possible prion disease in all but one case (diagnostic brain biopsy). Conclusion: Surgeries were common in patients with prion disease in this series and were commonly performed by operators who were unaware of the diagnosis. Coordinated approaches to screening and reporting may be needed to reduce the risk of iatrogenic spread of prion disease.